2021
DOI: 10.1101/2021.09.01.21262913
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sars-Cov-2 antibody titer 3 months post-vaccination is affected by age, gender, smoking and vitamin D

Abstract: Context Vaccination against Sars-Cov-2 is in full swing during COVID-19 pandemic. One of the efficient methods to evaluate response to vaccination is the assessment of humoral immunity by measuring Sars-Cov-2 antibody titer. Identification of factors that affect the humoral response is important so as to ameliorate the responses to vaccination or identify vulnerable groups that may need vaccination boosters. Objective We investigated the effect of anthropometric parameters (age, BMI), smoking, diabetes, statin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
4
2
Order By: Relevance
“…Similar observations were presented by Tsatsakis et al The results of their research showed that non-smokers had higher titers than smokers [ 70 ]. Our findings also agree with a recent study by Parthymou et al, who, based on a 3-month observation after full vaccination against COVID-19, indicated that smoking is associated with a lower humoral response [ 71 ]. Likewise, those observations confirm Nomura et al: in their study, three months after the second dose of the BNT162b2 vaccine, antibody titers were significantly lower in current smokers than in ex-smokers [ 72 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar observations were presented by Tsatsakis et al The results of their research showed that non-smokers had higher titers than smokers [ 70 ]. Our findings also agree with a recent study by Parthymou et al, who, based on a 3-month observation after full vaccination against COVID-19, indicated that smoking is associated with a lower humoral response [ 71 ]. Likewise, those observations confirm Nomura et al: in their study, three months after the second dose of the BNT162b2 vaccine, antibody titers were significantly lower in current smokers than in ex-smokers [ 72 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the authors found no effect of vitamin D status on the IgG response to vaccination through 21 weeks after the second dose [45]. In contrast, data from a longitudinal study of 712 subjects in Greece (mean age 51 years; 62% female) found that replete vitamin D levels were significantly associated with higher antibody titers 3 months post-vaccination with BNT162b2 [46]. Likewise, recently available preliminary data from Jolliffe et al also demonstrate an independent association between vitamin D supplement use and enhanced humoral responses to COVID-19 vaccination [47].…”
Section: Micronutrient Nutrition and Vaccine Responsescontrasting
confidence: 75%
“…Another report did not specify the enrolled population. In 17 out of 23 studies, current smokers showed significant lower antibody titre, and in a few reports, highlighted a more rapid lowering of the vaccine-elicited IgG compared with nonsmokers [19,20,[26][27][28][29][30]32,34,[36][37][38][39][40][41]43,44]. In particular, accelerated antibody decline was reported in the prospective assessments by Ferrara et al [20], Zhang et al [27], and Malavazos et al [30].…”
Section: Resultsmentioning
confidence: 92%